Clinical study of cardiac diseases during pregnancy - Kamat, Amitha Vijay; Dama, Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of the study was to evaluate the burden of cardiac diseases in pregnancy in our hospital, their clinical presentation, type of cardiac lesion, complications, maternal and neonatal outcome. Methods: A prospective analysis conducted at Karnataka Institute of Medical Sciences, Hubli, a tertiary care center in Karnataka, between July 2014 to June 2015. All patients with cardiac diseases during pregnancy and developed during postpartum period were included in the study. Age, parity, mode of delivery, perinatal outcome, complications intra-partum and post-partum were analyzed in detail. Results: 35 cases with cardiac disease in pregnancy were noted. Valvular heart disease accounted for 18 cases (51.4%), acyanotic CHD were 11 (31.4%) , cyanotic CHD were 2 (5.7%). 2 developed peripartum cardiomyopathy during their post natal period (5.7%) , 2 were admitted with previous history of peripartum cardiomyopathy. Most common lesion noted was mitral stenosis (40.5%). 26 had term deliveries and 7 had preterm. One maternal mortality was noted (2.8%). Conclusions: Cardiac diseases in pregnancy constitute high risk pregnancy and require special attention during antepartum, intrapartum and postpartum period. Rheumatic heart disease was the major contribution of cardiac diseases in pregnancy and is seen to be associated with increased maternal morbidity.